Bacterial Metabolism of Arylsulfonates: 1. Benzene Sulfonate as Growth Substrate for Pseudomonas testosteroni H-8 - Ripin, Marilyn J. (1971)
Pseudomonas testosteroni H-8 utilizes as sole carbon source benzene sulfonate (BS), p-toluene sulfonate (pTS), and ethylbenzene sulfonate (EBS) but not higher homologs. Growth on BS was rapid (generation time, 3 hr) and efficient (Y = 57), and resulted in accumulation of sulfate. As the culture is acid-sensitive, the medium must be heavily buffered to permit extensive growth. The BS oxidase system is inducible. Cells grown on BS, but not glutamate, oxidized BS, pTS, or EBS without lag (QO(2) = 50 to 100). Oxygen uptake on BS is temperature-dependent and sensitive to cyanide. Complete oxidation of 1 μmole of BS consumed approximately 5.7 μmoles of oxygen.